Psychiatry Residents in China: Socio-Demographic Characteristics, Career Satisfaction, and Related Factors - Jiang, Feng; Zhou, Huixuan; Hu, Linlin; Rakofsky, Jeffrey; Liu, Tingfang; Wu, Shichao; Liu, Huanzhong; Liu, Yuanli; Tang, Yi-lang (Frontiers in Psychiatry, 2019)
Objective: To study the socio-demographic characteristics, the working environment, and the amount of career satisfaction among psychiatry residents in China. Method: This was a part of a large-scale, nation-wide online survey of hospitals, healthcare professionals, and patients. Data, including socio-demographics, work hours, income, job satisfaction, and intention to quit were collected anonymously. Respondents also completed the Minnesota Satisfaction Questionnaire (MSQ). Results: One thousand and sixty residents nested in 32 psychiatric hospitals in 29 provinces in China completed the survey. Respondents were predominantly female (69.0%), worked an average of 47.8±11.6 hours per week, and 28.97% had experienced medical disputes in the previous year. The top three reported reasons for dissatisfaction were low pay (50.1%), contentious doctor-patient relationships (17.6%) and high workload (10.8%). An intention to quit their current job was reported by 18.7% of residents. The overall mean MSQ score was 73.8±13.8, with significant differences across post-graduate training year and regions. A multilevel regression analysis found that a higher MSQ score was significantly associated with fewer years in residency, shorter work hours, higher monthly pay, having medical liability insurance, and feeling satisfied with the level of doctor-nurse cooperation, their hospitals’ medical disputes prevention/management, and the healthcare workers’ social environment. Conclusion: Psychiatry residents in China are predominantly female and well-educated. They are only moderately satisfied with their career. Poor salaries, contentious doctor-patient relationships and high workload are among their top complaints and may explain why a considerable proportion are intending to leave their current residency. More support from the government regarding residents’ salaries, workload and working environment may help improve their job satisfaction and retention, ensuring that China will have a pool of well-trained and engaged psychiatrists for the future.